Towards caring for caregivers: assessing the burden of care and experience of associative stigma among caregivers of patients with chronic mental illnesses at a mental health care facility in Lagos Metropolis, Nigeria - Olagundoye, Olawunmi; Akhuemokhan, Victor; Alugo, Morenike (Family Medicine & Primary Care Review, 2017)
Background . Mental illness is becoming an inevitable part of life with an estimation of over 150 million cases occurring worldwide, commencing as early as age 15 and leading to disability and impairments. Caring for patients with chronic mental illnesses is increasingly becoming an unending fastidious task. The goal, which is often to help improve functioning and relieve symptoms, often places many demands and eventually leads to some form of burdensome experiences for the caregivers. The magnitude of this problem among caregivers, however, remains largely unknown in sub-Saharan Africa. Objectives . The study sought to describe the level and correlation of the burden experienced by caregivers in the families of patients with chronic mental illnesses, to determine the relationship between family functioning and the level of caregiver burden and, lastly, to determine the prevalence of stigma by association/family stigma in the study population. Material and methods . A total of 402 family caregivers of patients with chronic mental illnesses attending the outpatient clinics of the Federal Neuro-psychiatric Hospital, Yaba, were interviewed using a socio-demographic data collection sheet, family functioning (APGAR) scale, the Zarit Burden Interview (ZBI) instrument and questions measuring the psychological effects of being a relative of a patient with severe mental illness. Results. The results of the study showed that 42% of the subjects experienced a high level of burden, and this was significantly associated with the gender of caregivers, their level of education, familial relationship of the caregivers to the patients, income, distance of residence from a health facility, family functioning and experience of family stigma. Conclusions . Chronic mental illnesses are associated with a high level of caregiver burden in nearly half of the study population. A low level of income is an important predictor of high burden that could be addressed through occupational rehabilitation of patients and provision of employment with a view to improving family income. Introduction of support groups and continuous advocacy against stigmatisation of individuals with mental illnesses and their families are essential.